2021
DOI: 10.3390/pr9020225
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Enzyme Systems in Flow Chemistry

Abstract: Recent years have witnessed a growing interest in the use of biocatalysts in flow reactors. This merging combines the high selectivity and mild operation conditions typical of biocatalysis with enhanced mass transfer and resource efficiency associated to flow chemistry. Additionally, it provides a sound environment to emulate Nature by mimicking metabolic pathways in living cells and to produce goods through the systematic organization of enzymes towards efficient cascade reactions. Moreover, by enabling the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 148 publications
0
27
0
Order By: Relevance
“…Other researchers have also noted that immobilization improves enzyme stability in microwave fields [61,62]. A study by Cydzik-Kwiatkowska et al ( 2012) on the effect of microwaves on anaerobic biofilm found improved biodiversity after microwave exposure.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other researchers have also noted that immobilization improves enzyme stability in microwave fields [61,62]. A study by Cydzik-Kwiatkowska et al ( 2012) on the effect of microwaves on anaerobic biofilm found improved biodiversity after microwave exposure.…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, immobilization was found to promote enzymatic transesterification of (R,S)-2-octanol and non-thermal effects of microwave radiation [60]. Other researchers have also noted that immobilization improves enzyme stability in microwave fields [61,62].…”
Section: Resultsmentioning
confidence: 99%
“…163 Immobilization of single enzymes is now relatively routine and is applied in a wide range of commercial processes. 164 However, immobilization of multiple enzymes on a single material is unlikely to be optimal when using simple chemical bonds due to the varied chemistries of the support and the enzymes; 165 hence, more universal immobilization systems are sought. 166 To this end, alternative methods of enzyme immobilization have been developed using protein engineering, mostly affinity binding, and particularly through the creation of fusion proteins by combining surface binding regions and the enzyme of interest.…”
Section: Could Bementioning
confidence: 99%
“…Sequestration, encapsulation, protein-protein interactions, and surface attachments increase enzyme stability and activity, prevent degradation and increase reaction efficiency by creating local co-factor and substrate pools. Inspired by these mechanisms, new types of co-immobilization strategies are therefore increasingly developed that emphasize spatial organization via diverse scaffolding and compartmentalization approaches [18,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%